Answer:
I dont know
Step-by-step explanation:
multiple and simply the equation
Answer:
Step-by-step explanation:
Figure (1)
x° = 107° [Vertically opposite angles]
Since, vertical angles are equal in measure.
Figure (2)
x + 71° = 90° [Given, complementary angles]
x = 90° - 71°
x = 19°
Figure (3)
x + 21° = 180° [Given as supplementary angles]
x = 180° - 21°
x = 159°
Figure (4)
x = 129° [Vertical angles]
Figure (5)
x° = 90° [Given]
z° + 34° = 90°
z° = 90° - 34°
z° = 56°
Since, x° + y° + z° = 180° [Linear angles]
90° + y° + 56° = 180°
y° + 146° = 180°
y° = 180° - 146°
y° = 34°
K-12=28...? I think this is what your question is asking for
Answer:
f(x) = -x + 3
Step-by-step explanation:
To flip it over the y-axis, just make all your x-values negative.
y(x) = x + 3
f(x) = y(-x) = (-x) + 3 = -x + 3